Alternaria Toxins: Potential Virulence Factors and Genes Related to Pathogenesis - Meena, Mukesh; Gupta, Sanjay K.; Swapnil, Prashant; Zehra, Andleeb; Dubey, Manish K.; Upadhyay, Ram S. (Frontiers in Microbiology, 2017)
Alternaria is an important fungus to study due to their different life style from saprophytes to endophytes and a very successful fungal pathogen that causes diseases to a number of economically important crops. Alternaria species have been well characterized for the production of different host-specific toxins (HSTs) and non-host specific toxins (nHSTs) which depend upon their physiological and morphological stages. The pathogenicity of Alternaria species depends on host susceptibility or resistance as well as quantitative production of HSTs and nHSTs. These toxins are chemically low molecular weight secondary metabolites (SMs). The effects of toxins are mainly on different parts of cells like mitochondria, chloroplast, plasma membrane, Golgi complex, nucleus, etc. Alternaria species are produced from several nHSTs such as brefeldin A, tenuazonic acid, tentoxin and zinniol. HSTs that act in very low concentrations affect only certain plant varieties or genotype and play a role in determining the host range of specificity of plant pathogens. The commonly known HSTs are AAL-, AK-, AM-, AF-, ACR- and ACT-toxins which are named by their host specificity and these toxins are classified into different family groups. The HSTs are differentiated on the basis of bio-statistical and other molecular analyses. All these toxins have different mode of action, biochemical reactions and signalling mechanisms to cause diseases. Different species of Alternaria produced toxins which reveal its biochemical and genetic effects on itself as well as on its host cells tissues. The genes responsible for the production of HSTs are found on the conditionally dispensable chromosomes (CDCs) which have been well characterized. Different bio-statistical methods like BLAST data analysis used for the annotation of gene prediction, pathogenicity-related genes may provide surprising knowledge in present and future.